2013
DOI: 10.1016/j.canep.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, metformin use, and colorectal cancer survival in postmenopausal women

Abstract: Background Observational studies have associated metformin use with lower colorectal cancer (CRC) incidence but few studies have examined metformin’s influence on CRC survival. We examined the relationships among metformin use, diabetes, and survival in postmenopausal women with CRC in the Women’s Health Initiative (WHI) Clinical Trials and Observational Study. Methods 2,066 postmenopausal women with CRC were followed for a median of 4.1 years, with 589 deaths after CRC diagnosis from all causes and 414 deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 22 publications
2
51
0
Order By: Relevance
“…Previous studies have attempted to identify the effect of diabetes and metformin on both cancer-specific and overall mortality in crc patients, but with varying results 17,[29][30][31][32] . One focused on postmenopausal women only, another did not examine specific diabetes treatments, and the remaining studies did not provide a comparison to a nondiabetic control group [17][18][19]33,34 . Other studies, including a recent meta-analysis looking at the role of metformin with respect to cancer risk and mortality, suggested that metformin could reduce the risks, but did not assess the effect of tumour stage 35,36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have attempted to identify the effect of diabetes and metformin on both cancer-specific and overall mortality in crc patients, but with varying results 17,[29][30][31][32] . One focused on postmenopausal women only, another did not examine specific diabetes treatments, and the remaining studies did not provide a comparison to a nondiabetic control group [17][18][19]33,34 . Other studies, including a recent meta-analysis looking at the role of metformin with respect to cancer risk and mortality, suggested that metformin could reduce the risks, but did not assess the effect of tumour stage 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Although strong evidence supports the association of diabetes with crc, and recent work has examined metformin as a prognostic factor in crc, results are contradictory and tend to be related to specific patient populations [15][16][17][18][19] . In the present retrospective study, we set out to investigate whether metformin use in diabetic patients diagnosed with crc was associated with survival.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate analysis of 212 postmenopausal women with colorectal cancer and type 2 diabetes, no statistically significant difference in colorectal cancer-specific survival was observed among users of metformin compared to non-users (HR 0.75, 95% CI 0.40-1.38) although unfortunately, the authors of this study were unable to obtain data on the timing of metformin use in relation to colorectal cancer diagnosis. 28 Other epidemiological studies investigating metformin use after colorectal cancer diagnosis and all-cause mortality and have indicated a beneficial effect with metformin use, 11,12 however these investigations are limited by small sample size and the use of only one exposure timepoint. Moreover, findings from studies which only examine the impact of metformin on all-cause mortality may be reflective of non-cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…30-35 ) associated with metformin exposure must be balanced against others that do not show such associations (e.g., refs. [36][37][38][39]. Some studies suggest unexpected variables that might modify the effects of metformin, including pharmacoepidemiologic evidence that exposure to both a statin drug and metformin is necessary for an important antineoplastic effect to be observed ( 40 ) and laboratory evidence that administration of proton pump inhibitors limits cellular uptake of metformin ( 41 ).…”
Section: Pharmacoepidemiology: Hypothesis-generating Cluesmentioning
confidence: 99%